Proposição de um modelo para mensurar o nível de prontidão de uma indústria para a implementação da indústria 4.0 - Rodrigues, Thales Volpe (2021)
Industry 4.0 is a concept used to describe a new industrial paradigm that encompasses a set of future industry developments related to enabling technologies. The adoption of these technologies is fundamental for the development of the new manufacturing process. The Industry 4.0 concept gains momentum and implies a significant qualitative leap in organizations. Thus, the academic literature has been paying more and more attention to this theme. Given this context, this work aims to develop a model to measure the level of readiness of industries to implement Industry 4.0. For this, a bibliographic portfolio was built to be used as a theoretical basis for the research, through a literature review using the Methodi Ordinatio. The articles used were reviewed bibliometrically with the help of the VosViewer software, and their content was through the QSR Nvivo [trade mark] version 10 software. These analyzes were important for the construction of a theoretical model of readiness analysis, divided into 2 aspects of the industry (organizational and operational) and 10 dimensions (Culture, processes, products, technologies, culture, strategy, infrastructure, leadership, human resources and governance), being evaluated in terms of the 55 prerequisites for the implementation of Industry 4.0. The model is supported by the AHP method, where the weights of aspects and dimensions were defined, based on the answers of experts in Industry 4.0. Thus, the proposed model was applied with 19 company managers from 4 Brazilian states (Minas Gerais, São Paulo, Rio de Janeiro and Paraná). It was later applied to companies seeking to develop technologically. The readiness assessment is divided into 5 levels, where level 1 shows that the company has a very low readiness and level 5 an advanced state of readiness for Industry 4.0. From a company size perspective, it was noted that small and mediumsized companies are at level 3, while large companies have level 4 of readiness. In general, the industries presented at level 4 of readiness, highlighting the large companies and companies from Paraná. It was thus noted that a culture open to innovation, employee training and a welldefined strategy for implementing Industry 4.0 can be an important factor for technological development.